Telemonitoring in Chronic Heart Failure: A Systematic Review. (7th June 2012) - Giamouzis, Gregory; Mastrogiannis, Dimos; Koutrakis, Konstantinos; Karayannis, George; Parisis, Charalambos; Rountas, Chris; Adreanides, Elias; Dafoulas, George E.; Stafylas, Panagiotis C.; Skoularigis, John; Giacomelli, Sara; Olivari, Zoran; et al.
Abstract : Heart failure (HF) is a growing epidemic with the annual number of hospitalizations constantly increasing over the last decades for HF as a primary or secondary diagnosis. Despite the emergence of novel therapeutic approached that can prolong life and shorten hospital stay, HF patients will be needing rehospitalization and will often have a poor prognosis. Telemonitoring is a novel diagnostic modality that has been suggested to be beneficial for HF patients. Telemonitoring is viewed as a means of recording physiological data, such as body weight, heart rate, arterial blood pressure, and electrocardiogram recordings, by portable devices and transmitting these data remotely (via a telephone line, a mobile phone or a computer) to a server where they can be stored, reviewed and analyzed by the research team. In this systematic review of all randomized clinical trials evaluating telemonitoring in chronic HF, we aim to assess whether telemonitoring provides any substantial benefit in this patient population.